2022
DOI: 10.1002/mbo3.1298
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the principles and methods underlying the recovery of metagenome‐assembled genomes from metagenomic data

Abstract: The rise of metagenomics offers a leap forward for understanding the genetic diversity of microorganisms in many different complex environments by providing a platform that can identify potentially unlimited numbers of known and novel microorganisms. As such, it is impossible to imagine new major initiatives without metagenomics. Nevertheless, it represents a relatively new discipline with various levels of complexity and demands on bioinformatics. The underlying principles and methods used in metagenomics are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 181 publications
0
7
0
Order By: Relevance
“…During the magnetic enrichment step, fast-swimming cells with more efficient magnetotactic behavior, such as magnetotactic cocci within the Magnetococcia, are more preferentially enriched compared to those slow swimming populations with less efficient magnetotaxis 33 . Apart from magnetic cell enrichment, bias could also be introduced during the following 16S rRNA gene amplification or whole genomic DNA amplification processes [66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…During the magnetic enrichment step, fast-swimming cells with more efficient magnetotactic behavior, such as magnetotactic cocci within the Magnetococcia, are more preferentially enriched compared to those slow swimming populations with less efficient magnetotaxis 33 . Apart from magnetic cell enrichment, bias could also be introduced during the following 16S rRNA gene amplification or whole genomic DNA amplification processes [66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, metagenomic shotgun sequencing has been used to study gene functions in the bacterial ora. However, metagenome shotgun analysis involves binning to identify bacterial species and then constructing a metagenome-assembled genome to search for gene distribution [44]. Although the binning technology has improved and contributed to the identi cation of many bacteria, the high homology of essential genes among species makes complete classi cation extremely di cult.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the possible influence of the enrichment conditions on the growth of the two strains, the limits that were determined in this study are more related to the post-enrichment steps, including DNA extraction, library preparation, data acquisition, and data processing [ 29 ]. It has been shown that the DNA extraction procedure can affect the structure of the population, especially in these particular conditions where high quantities of high-molecular-weight DNA are required (MinION sequencing from complex matrices) [ 30 ]. Similarly, according to the properties of the DNA (for example, GC content), the library preparation step performs differently [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%